Low urinary selenium concentration is associated with nonthyroidal illness syndrome in hospitalized patients with COVID-19 - Sara Moreira Anunciação; Renata de Oliveira Campos; Fabyan Esberard de Lima Beltrão; Déborah Araújo Morais; Wellington Tavares de Sousa Júnior; Fernando Barbosa Júnior; Jéssica Fernanda Cassemiro; Pedro Resende Ferreira Rende; Fabio Hecht; Helton Estrela Ramos (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: This study aimed to assess urinary selenium concentration (USC) and its correlation with non-thyroidal illness syndrome (NTIS) and inflammatory markers in hospitalized adult patients with COVID-19. Subjects and methods: A prospective study was conducted to investigate urinary selenium (Se) concentration in adult patients hospitalized with COVID-19 between June and August 2020. Urine and serum samples were collected before complications occurred, always within the first 48 hours after onset. A total of 121 patients were stratified into three tertiles based on USC: (i) USC < 25 μg/L (40), (ii) USC 25-39 μg/L (41), and (iii) USC > 39 μg/L (40). ICP-MS was employed to measure urinary Se concentration. NTIS was defined by free triiodothyronine below 2.3 pg/L accompanied by low or normal thyroid-stimulating hormone levels. Results: NTIS was observed in a low prevalence (5.7%) and was significantly associated with patients having the lowest USC (n = 6, p = 0.008). Thyroiditis was the most prevalent thyroid complication (23.9%); however, there was no significant association with USC (p > 0.05). Conclusion: The association between low USC and NTIS was evident in this cohort.